2011
DOI: 10.1073/pnas.1103904108
|View full text |Cite
|
Sign up to set email alerts
|

Differential transformation capacity of Src family kinases during the initiation of prostate cancer

Abstract: Src family kinases (SFKs) are pleiotropic activators that are responsible for integrating signal transduction for multiple receptors that regulate cellular proliferation, invasion, and metastasis in a variety of human cancers. Independent groups have identified increased expression of individual SFK members during prostate cancer progression, raising the question of whether SFKs display functional equivalence. Here, we show that Src kinase, followed by Fyn kinase and then Lyn kinase, exhibit ranked tumorigenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 37 publications
(56 reference statements)
4
81
0
Order By: Relevance
“…Our observation of SRC activity supports previous work that this kinase synergizes with other genes, including AR, to contribute to prostate adenocarcinoma (18,51). SRC has also been shown to interact with the intracellular region of ERBB2 (HER-2), supporting the notion that SRC may be an important node for targeted therapy in advanced prostate cancer (17,52).…”
Section: Discussionsupporting
confidence: 78%
“…Our observation of SRC activity supports previous work that this kinase synergizes with other genes, including AR, to contribute to prostate adenocarcinoma (18,51). SRC has also been shown to interact with the intracellular region of ERBB2 (HER-2), supporting the notion that SRC may be an important node for targeted therapy in advanced prostate cancer (17,52).…”
Section: Discussionsupporting
confidence: 78%
“…Recent in vivo studies have shown that LYN knockout or hyperactivation animal models provide compelling evidence that LYN cannot have possibility to initiate neoplasia. 20,29,51 However, accumulated evidence has indicated that LYN plays a role in tumor progression. 52,53 These investigations elucidated that LYN plays an oncogenic role in these tumors, and promotes the tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…6 and includes FYN, a known prostate cancer oncogene with a role in cell invasion (27,28), and MOXD1, a gene up-regulated in primary compared with metastatic prostate cancer (29). These genes are bound by ERG proximally or distally (Fig.…”
Section: Nonmentioning
confidence: 99%